Why bayes rules: A note on Bayesian vs. classical inference in regime switching models - Dennis Gärtner (University of Zurich, Socioeconomic Institute, 2007)
By means of a very simple example, this note illustrates the appeal of using Bayesian rather than classical methods to produce inference on hidden states in models of Markovian regime switching.
Keywords: C11; C22; 330; Bayesian analysis; switching regression; regime changes; nonlinear filtering; Bayes-Statistik; Inferenzstatistik; Markovscher Prozess; Modellierung